The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1634/stemcells.2007-0122
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neurogenesis and Astrogenesis from Neural Progenitor Cells Grafted in the Hippocampus of GFAP−/−Vim−/− Mice

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…Our results showed that all VCCs in the lateral, the anterior and the posterior horn (outside of the EZ) of the spinal cord of G93A SOD1 transgenic mice overlapped to express GFAP; thus, it is suggested that an increase in the numbers of VCCs represents astrogenesis [30] and an astrocyte regenerative response from VCCs occurred in the spinal cord of ALS disease-like transgenic (G93A SOD1) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that all VCCs in the lateral, the anterior and the posterior horn (outside of the EZ) of the spinal cord of G93A SOD1 transgenic mice overlapped to express GFAP; thus, it is suggested that an increase in the numbers of VCCs represents astrogenesis [30] and an astrocyte regenerative response from VCCs occurred in the spinal cord of ALS disease-like transgenic (G93A SOD1) mice.…”
Section: Discussionmentioning
confidence: 99%
“…5K). The expression of glial markers, including GFAP and VIM (36,37), remained almost unaltered following ZMYND8 silencing (Fig. 5K).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 96%
“…Thus the development of drugs that target the classical cascade may be a useful treatment for the neurodegenerative conditions. Double GFAP and vimentin knockout mice have fewer surviving astrocytes and neurons derived from a transplant of neural progenitor cells into the hippocampus (Widestrand et al, 2007). This may suggest that reactive astrocytes can prime areas of the CNS to allow the survival of neuro-precursor cells or allow the integration of these cells into astrocytes and neurons at sites of injury.…”
Section: Chronic Astrogliosismentioning
confidence: 99%